Mechanical Properties And Durability Performance Of POFA-Based Engineered Alkali-Activated Cementitious Composites - Abiodun, Salami Babatunde (2018)
Palm oil fuel ash (POFA) has been partially used over the years in developing concrete and mortar. However, to save the environment of POFA waste from dumpsites causing health issues and to reduce the consumption of Portland cement, 100% POFA was used in this study. The properties and performance of POFA alkali-activated mortar and POFA engineered alkali-activated cementitious composite (POFA-EACC) have been studied. The aim of the research is to develop POFA-EACC with good mechanical strength and better matrix durability properties. This aim was achieved through the utilization of POFA as the only base material for the POFA-EACC. The study encompasses the suitability evaluation of POFA alkali-activated mortar matrix (without polyvinyl alcohol (PVA) fibers) for POFA-EACC, the durability performance of the alkali-activated mortar matrix and the composite mechanical performance of the POFA-EACC (with PVA fibers). The alkali-activated mortar mixtures were prepared with different NaOH molarities (10, 12 and 14M), Na2SiO3(NS)+NaOH(NH)/POFA ratios of 0.4, 0.5 and 0.6, NS/NH ratios of 2.5, 2, 1 and 0.5, constant sand/POFA ratio of 1.5 and 2% volume fraction for PVA fibres (for POFA-EACC) were used. The results revealed a huge potential in the use of POFA as base material for alkaline activation. The optimum mixture consists of design parameters: NS/NH = 2.5, (NS+NH)/POFA = 0.4 and NaOH molarity = 10M. The highest compressive strength of 23.47 MPa and approximately 25 MPa were recorded after just three days and 28 days of curing respectively. The developed POFA alkali-activated binder has as its main products, N-A-S-H gel with some C-(A)-S-H gel forming in tandem within the alkali-activated mortar microstructure. Attempt were also made to improve the compressive strength of low-alumina POFA alkali-activated binder through the addition of different percentages of Al(OH)3, but results showed some losses in strength. The compressive strength of the optimum mixture reduced from approximately 25 MPa to 18 MPa, the lowest with the Al(OH)3 addition. In addition, the POFA alkali-activated mortar performed excellently in durability with H2SO4 and MgSO4 exposures in comparison to Na2SO4, HCl and HNO3. The obtained results were in agreement with the SEM/EDS, XRD and FTIR analyses. In addition, the tensile and flexural properties of POFA-EACC is very much dependent on the properties of POFA alkali-activated mortar and the interfacial bond between the POFA mortar matrix and PVA fibres. The uniaxial compressive strength of POFA-EACC reduced in comparison with those without PVA fibers due to the fibre-POFA matrix interface weakness. Although the POFA-EACC showed appreciable ductility as revealed in the tensile strain capacity results, the ultimate tensile and first cracking strength is generally low. Generally, the mixture parameters especially the NaOH molarity and water content greatly influenced all the properties of the POFA-EACC.